Circadian rhythms in the activity of a plant protein kinase. - Carter, P J (1991)
Bryophyllum fedtschenkoi is a Crassulacean acid metabolism plant whose phosphoenolpyruvate carboxylase is regulated by reversible phosphorylation in response to a circadian rhythm. A partially purified protein kinase phosphorylated phosphoenolpyruvate carboxylase in vitro with a stoichiometry approaching one per subunit and caused a concomitant 5- to 10-fold decrease in the sensitivity of the carboxylase to inhibition by malate. The sites phosphorylated in vitro were identical to those phosphorylated in intact tissue. The activity of the protein kinase was controlled in a circadian fashion. During normal diurnal cycles, kinase activity appeared between 4 and 5 h after the onset of darkness and disappeared 2----3 h before the end of darkness. Kinase activity displayed circadian oscillations in constant environmental conditions. The activity of protein phosphatase 2A, which dephosphorylates phosphoenolpyruvate carboxylase, did not oscillate. Treatment of detached leaves with the protein synthesis inhibitors puromycin and cycloheximide blocked the nocturnal appearance of the protein kinase activity, maintained phosphoenolypyruvate carboxylase in the dephosphorylated state and blocked the circadian rhythms of CO2 output that is observed in constant darkness and CO2-free air. The simplest explanation of the data is that there is a circadian rhythm in the synthesis of phosphoenolpyruvate carboxylase kinase.